Peran Laboratorium Ilmu Pengetahuan Alam (IPA) Dalam Pembelajaran IPA Madrasah Ibtidaiyah (MI) / Sekolah Dasar (SD) - Maya Agustina (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
The laboratory is a place equippep with tools and materials that are utilized in experiment. Natural science is one of the subjects in the curriculum of basic education level. Natural science is a dicipline that is dynamic and always evolving in accordance with the advancement of science and technology. The implementation of the practical method in learning natural science needs laboratory as a place to do practical work activities. The utilization of laboratory for practical activities is part of the teaching and learning proces. Through practical activities, students can examine the existing concepts or theories andexperience a process or experiment, then make the conclusions. This activity will support students undestanding towards the subject matter. Experiment is one of the methods of learning that can foster students sense of curiousity, creativity, innovation and scientific honesty in dealing with an real life issues. The laboratory has a very important role in learning natural science at the level of primary education as in Madrasah Ibtidaiyah (MI)/ Sekolah dasar (SD).